Comparative analysis of nasal mucociliary clearance in healthy tobacco smokers and non-smokers in Abuja, Nigeria: implications for respiratory health - Edevbie, Ifeoma C.; Ojimadu, Chinwe I.; Olusesi, Abiodun D.; Andrew, Imogu O. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Nasal mucociliary clearance (NMC) is a crucial airway defense mechanism. Tobacco smoke, with its noxious components, impairs NMC, predisposing individuals to sinonasal diseases. Limited research exists in sub-Saharan Africa, where environmental and genetic factors may further influence NMC. The primary objective of this study was to investigate the effect of tobacco smoking on nasal mucociliary clearance time (NMCT) in healthy adults in Abuja, Nigeria, comparing smokers to non-smokers. Methods: A community-based, prospective cross-sectional study was conducted on adults aged 18-45 in Abuja, Nigeria. Participants completed questionnaires on smoking history, medical history and comorbidities. Anterior rhinoscopy was performed, followed by a saccharine transit time test to measure NMCT in minutes. Results: Three hundred and four (304) participants were recruited, with 152 (50%) smokers (60 smoked both cigarette and shisha, 55 shisha only, 37 cigarette only) and 152 (50%) non-smokers. The mean age was 30.7±6.3 years (smokers: 30.2±6.7; non-smokers: 31.3±5.9). Smokers had a significantly prolonged mean NMCT (14.96±3.75 minutes) compared to non-smokers (8.25±2.02 minutes) (t=20.197, p<0.001). Significant differences were found between all smoking groups and the non-smoker group (cigarette only: 17.08±2.69 minutes; both: 16.45±2.95 minutes; shisha only: 11.91±2.47 minutes; control: 8.25±2.02 minutes) (F=246.152, p<0.001). There was no significant difference in NMCT between those smoking both cigarette and shisha and those smoking only cigarettes (p=0.603). Conclusions: Tobacco smoking significantly prolongs Nasal Mucociliary Clearance Time (NMCT), with cigarette-only smokers exhibiting the longest NMCT, followed by combined cigarette and shisha smokers and then shisha-only smokers.